Architectural semiotics to uncover the denotative and connotative meanings of buildings in Malioboro, Yogyakarta (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This study examines the denotative and connotative meanings of architectural elements in historical buildings on Malioboro Street, Yogyakarta, using Roland Barthes' semiotic approach. The Malioboro shopping area has undergone modernization, impacting the function and public interpretation of its buildings. This research aims to understand the existing visual forms in logos, exteriors, and interiors contribute to constructing architectural meaning and how visitors interpret these signs in cultural and historical contexts. The research method involves direct observation and structured interviews with 12 respondents, consisting of both new and returning visitors. The analysis focuses on six selected buildings that have retained their original architectural form. The findings indicate that denotative meaning is more easily recognized than connotative meaning. Logos and exteriors play a more significant role in communicating explicit meanings, while interiors contribute more to conveying symbolic meanings. These findings emphasize the importance of preserving historical architectural elements to maintain cultural identity and symbolic heritage in Malioboro through visitors' collective experience and perception of the area. Implications for architectural science, this research enriches architecture by bridging the gap between physical form and socio-cultural meaning. This approach not only optimizes the function of space but also makes architecture a medium of communication that is relevant to the context of the times.
Keywords: Architectural semiotics; Connotation; Denotation; Malioboro; Roland Barthes